Dimensões do eu contemporâneo nos quadrinhos autobiográficos - Ramiro, Clívia (2014)
The comics autobiography is a narrative form capable of providing significant views on the self-expression of the man identity and conflicts in the contemporaneousness. This dissertation objective is to study the dimensions assumed by the self of the autobiographic comics, having as corpus the Holocaust testimony in Europe on the 20th century first half, in Maus, by Art Spiegelman(2009); and the familiar disintegration linked to the Brazilian social inequalities nowadays, in Memória de elefante, by Caeto ( 2010). In a context of multiple times and spaces, plurilinguism, metanarrativity, ex-centricity and dilution of the self, the problem which emerges is how the selected graphic novels answer, in their singular syntax, on the contemporary complexity in the autobiographic structure. The hypothesis is that it is possible to apprehend, in autobiographic comics from two different cultures, a common yearning by a self that confront the oppression devices through subjectivation and desubjectivation authorial processes. This research theoretical basis was: Santaella (2012), Eisner (2001, 2005 and McCloud (2004, 2006) for the comics language reading; Lejeune (2008), Miraux (1996), Nigro, Busato e Amorim (2010) for autobiographic topics; Todorov (1982, 2010), Benjamin (1994, 2006) and, specially, Agamben (2007, 2008, 2010) for the contemporary narrative and the (de)subjectivation matters. According to the analysis, our conclusion is that is a fundamental compositional difference between the two autobiographies: the way the author configures his disappearance and dessubjectivates himself in Maus, in opposition to the identity strengthening and subjectivation, in Memória de elefante, as a reaction to the power devices in the urban centers. Although they have different time and space perspectives, the Spiegelman and Caeto autobiographies keep in common the indissolubility between social critics and traumatic personal experiences. They are composed by subjects that live, narrate and write the trajectories of selves who do not fit in themselves anymore, and face, through the comics narrative art, the devices which annihilate the contemporary subject